A study on unsteady flow through porous media : A cubic spline collocation approach. Issue 5 (4th July 2021) - Shah, Pinky; Tandel, Priti; Prajapati, Jyotindra
Abstract: An analysis carried out to study unsteady flow through porous media. The non-linear equation governing the flow problem is transformed into linear differential equation using quasi linearization technique and solved by applying cubic spline collocation method. The obtained numerical results are compared with finite difference method to show the effectiveness and accuracy of the method.